Suicidal ideation and associated factors among people living with HIV/AIDS in Ethiopia: a systematic review and meta-analysis - Gebrekidan, Amanuel Yosef; Lombebo, Afework Alemu; Efa, Amelework Gonfa; Azeze, Gedion Asnake; Kassie, Gizachew Ambaw; Haile, Kirubel Eshetu; Asgedom, Yordanos Sisay; Woldegeorgis, Beshada Zerfu; Dejenie, Tadesse Asmamaw (Frontiers in Psychiatry, 2024)
Background Suicide is one of the main causes of mortality in the world, accounting for more fatalities than homicide, war, human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), breast cancer, and malaria. Significantly, the biggest risk factors for suicide in the general population are having already attempted suicide and suicidal ideation. Despite the availability of studies on suicidal ideation among people living with human immunodeficiency/acquired immunodeficiency syndrome in Ethiopia (PLWHA), the results are inconsistent, thus a systematic review and meta-analysis were conducted to estimate the pooled prevalence of suicidal ideation among PLWHA. Methods A systematic review and meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. To find papers published in the English language before May 20, 2023, the electronic databases of Medline, Science Direct, Excerpta Medica Database, Cochrane Library, African Journals Online (AJOL) and Google scholar were searched. The DerSimonian and Laird method for random effects models was used to estimate the pooled prevalence of suicidal ideation with a 95% CI in STATA V.14.0 statistical software. To test for heterogeneity between studies and publication bias, respectively, forest plots and funnel plots were used. Additionally, leave-one-out sensitivity was conducted. Results A total of nine studies with 3411 study participants were included in this systematic review and meta-analysis. The pooled prevalence of suicidal ideation among PLWHA was 20.55% (95% CI 14.76, 26.33). Being female (OR = 4.27, 95% CI = 2.29, 7.97), living alone (OR = 5.02, 95% CI = 2.15, 11.64), poor social support (OR = 3.80, 95% CI = 2.56, 5.65), perceived stigma (OR = 3.50, 95% CI = 1.55, 7.87), depression (OR = 5.08, 95% CI = 2.55, 11.48), undisclosed HIV status (OR = 4.8, 95% CI = 2.10, 10.93) and World Health Organization (WHO) clinical stages of III or IV (OR = 4.40, 95% CI = 2.95, 6.58) were significantly associated with suicidal ideation. Conclusion Suicidal ideation among PLWHA is high in Ethiopia. Therefore, emphasis should be given to psychiatric assessment and interventions, with a special focus on individuals with the associated factors.